2019
DOI: 10.26434/chemrxiv.9943943
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensitive Mechanocontrolled Luminescence in Cross-Linked Polymer Films

Abstract: Direct translation of mechanical force into changes in chemical behavior on a molecular level has important implication not only for the fundamental understanding of mechanochemical processes, but also for the development of new stimuli-responsive materials. In particular, detection of mechanical stress in polymers via non-destructive methods is important in order to prevent material failure and to study the mechanical properties of soft matter. Herein, we report that highly sensitive changes in photoluminesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Due to our interest in exploring mechanoresponsive materials such as polymer lms modied with co-polymerized photoluminescent metal complexes, 25 we decided to see if TL properties can also be observed when these triboluminescent Cu(NHC) complexes were blended into amorphous polymer lms. Using polymer lms may provide a convenient way to make bulk mechanoresponsive material or coating via simple synthetic methods, avoiding the limited repeatability and fabrication method limitations associated with the use of a crystalline solid.…”
Section: Triboluminescent Properties In Amorphous Polymer Lmsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to our interest in exploring mechanoresponsive materials such as polymer lms modied with co-polymerized photoluminescent metal complexes, 25 we decided to see if TL properties can also be observed when these triboluminescent Cu(NHC) complexes were blended into amorphous polymer lms. Using polymer lms may provide a convenient way to make bulk mechanoresponsive material or coating via simple synthetic methods, avoiding the limited repeatability and fabrication method limitations associated with the use of a crystalline solid.…”
Section: Triboluminescent Properties In Amorphous Polymer Lmsmentioning
confidence: 99%
“…This is in contrast to previously reported NHC Cu I complexes cross-linked into elastomeric, stretchable polybutylacrylate lms, which do not show detectable triboluminescence. 25 Thus, these ndings represent the rst example of Cu complexes that display TL properties when simply blended into amorphous polymer lms. 53 There are several reports on TL polymers lms containing Eu complexes.…”
Section: Triboluminescent Properties In Amorphous Polymer Lmsmentioning
confidence: 99%
See 1 more Smart Citation
“…[176] Finally, these mechanoresponsive complexes were also used as cross-linkers in poly(butyl acrylate) (PBA), and spectroscopic analysis of samples during deformation showed that stresses as low as 0.1 MPa could be detected, providing further evidence for the sensitivity of the organometallic complexes to mechanical stimuli. [177] Moreover, the emission wavelength of [CuN 4 -NHC](BF 4 ) was successfully tuned by modifying the excited state geometry, i.e., by employing an NHC ligand with bulky diisopropyl (DIP) moieties. [178] PUs in which this complex was covalently integrated responded to tensile elongation by an increase in PL intensity as well as a blue shift of the emission band, which was attributed to an increasing separation of the BF 4 − counterion from the complex as the surrounding polymer matrix deformed.…”
Section: Organometallic Complexes As Mechanoresponsive Moietiesmentioning
confidence: 99%
“…[8] However, the exact force acting on a mechanophore is difficult to ascertain, as many factors during cavitation or within a material influence the transmittance of the force to the mechanophore, such as the molecules overall rigidity, [3f,9] the length of attached residues [10] or the material's morphology. [11] Thus, recent activities on metallocenes, [7] Cu-pyridine, [12] and BÀ N bonds [13] demonstrated metal/ligand-cleavage in polymeric bulk-systems or in solution, which finally did not allow for a precise, direct quantification of the individual metal/ligandbond upon mechanical stressing.…”
Section: Introductionmentioning
confidence: 99%